1970
DOI: 10.1159/000175288
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Formulas in the Treatment of Phenylketonuria in Infants

Abstract: The use of a whey protein formula as natural protein source in the dietary treatment of two infants with phenylketonuria is described. Two practical advantages were found. Firstly, the whey protein formula had the same caloric and nitrogen content as the special low-phenylalanine formula, which made adjustments of the intake of these two formulas in order to balance the phenylalanine intake easy. Secondly, since the whey protein formulas had a lesser phenylalanine content than whole milk protein, which is usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1972
1972
1979
1979

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Most authors use ordinary milk for this purpose. However, H ambraeus et al [1] recently reported the practical advantages of using whey protein-containing formulas as a natural protein source. Since whey proteins contain less phenylalanine than casein, this means feeding a larger amount of natural protein to the patients and using a lesser amount of the artificial phenylalanine-free or low preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors use ordinary milk for this purpose. However, H ambraeus et al [1] recently reported the practical advantages of using whey protein-containing formulas as a natural protein source. Since whey proteins contain less phenylalanine than casein, this means feeding a larger amount of natural protein to the patients and using a lesser amount of the artificial phenylalanine-free or low preparation.…”
Section: Introductionmentioning
confidence: 99%
“…In 1970 Hambraeus et al (7) reported the practical advantages of using a humanized cow milk formula as a natural source of protein in the treatment of phenylketonuria (PKU). In this formula, the amount of whey protein in relation to casein is the same as in human breast milk, i.e.…”
mentioning
confidence: 99%
“…60:40. It was shown that this formula constituted about 55 % of the nitrogen intake in an infant with PKU (7). In their studies on the fractionation and biological evaluation of a whey protein concentrate, Forsum and Hambraeus (3) calculated that a whey protein concentrate low in phenylalanine as a source of natural protein covered almost 80 % of the nitrogen intake in an infant with PKU.…”
mentioning
confidence: 99%